Assessing Mathematical School Readiness - Mejias, Sandrine; Muller, Claire; Schiltz, Christine (Frontiers in Psychology, 2019)
Early mathematical abilities matter for later formal arithmetical performances, school and professional success. Accordingly, it seems central to accurately assess numerical school readiness at school entrance. This is a prerequisite for identifying school-starters who are at risk to encounter difficulties in mathematics and stimulate their acquisition of mathematical fundamentals as soon as possible. In the present study, we present a new test which allows professionals working with children (e.g., teachers, school psychologists, speech therapists, school doctors) to assess children’s numerical school readiness when they enter formal schooling in a simple, rapid and efficient manner. 346 children were assessed at the entrance of 1st grade (6-to-7-year-olds) with the novel numerical school readiness test (T1). In addition, children’s numerical skill levels were evaluated with classical arithmetical tests at T1 and a year later in 2nd grade (T2, 7-to-8-year-olds). Performance in these classical tests in 1st and 2nd grade systematically related to their early mathematical abilities assessed with the numerical school readiness test. By using the present test to evaluate numerical school readiness it is possible to identify pupils at risk for developing poor mathematical skills right from the start of formal schooling. Such a tool is needed, as a child’s scholastic level in mathematic at school entrance (or school readiness) is known to be critical for his or her future school and professional carrier (Currie & Thomas, 1999; Duncan et al., 2007; Pagani, Fitzpatrick, Archambault, & Janosz, 2010; Rivera-Batiz, 1992; Romano, Babchishin, Pagani, & Kohen, 2010).